Treatment of Contaminated Collected Wastwater at Petroleum Fuel Filling Stations for Using as Make Up Water for Cooling Tower in Petroleum Refineries - Ahmed, Thabit A.; Ayob, Saba S.; Shahatha, Mohammed A.; Khorsheed, Shaymaa R.; Mohammed, Mohammed J. (Journal of Petroleum Research and Studies, 2023)
The collection of washing wastewater (oily water) in petroleum service stations represents an environmental problem particularly after the introducing of cars washing stations to the petroleum station site. The generated water from washing and maintenance of the petroleum stations, rain water is collected in the storage tank. This water contains hydrocarbons and suspended solids with high organic load. Discarding this type of water to the water bodies like rivers without treatment causes increasing of pollution. This study aims to manage generated wastewater in petroleum service stations successfully by using methods keeping the source of water and protect the environment from the pollution. Alsmood and Alnaher petroleum stations which are located at the east of Baghdad were taken as case study. A mixed sample of wastewater from both two stations was prepared. The sample was fully tested to study the expected specifications of water.The mixed samle was underwent to many treatement stages(oil skimming,coagulation-flocculation, sand filteration).The oil concentration of the raw smixed sample was decreased from (5% , 50000mg/L) to 1mg/L . The turbidity value was reduced after filteration from 175 to 1.4 NTU and also the total suspended solids(TSS) was decreased from 272 mg/L to 4 mg/L. The chemical oxygen demand (COD) underwent reduction during wastewater treatment from 730 to 44 mg O2 /L . Badse on the research fndings,the proposed scenario to manage the watstewater is installing a wastewater (oily water) treatment plant with 100m3/day capacity next to Aldura refinery in Baghdad to treat the water for reusing application as a make-up water for the cooling towers.